Physical Properties and Antigenic Components of Oriboca Virus - Karabatsos, N. (1973)
Two complement fixation (CF) components were detected in all of the various preparations (mouse liver, brain, serum, and BHK-21 cell culture) of Oriboca examined by equilibrium density centrifugation. The CF components possessed a buoyant density of 1.21 and 1.18 g/ml, and they were precipitated by treatment with protamine. Analysis of Oriboca virus by rate zonal sedimentation separated three components. The most rapidly sedimenting component was the infectivity which cosedimented with a peak of hemagglutinating (HA) activity designated VHA. A second, more slowly sedimenting, noninfectious HA component (HA-2) was followed by a peak of CF activity which barely moved from the top of the gradient. The single rate zonal CF peak and the two density gradient CF components were broadly cross-reactive serologically with Murutucu antiserum. They could not be identified as Oriboca on the basis of their CF reactions with Murutucu and Oriboca antisera. Oriboca-infective virions possessed an equilibrium density of 1.20 g/ml if derived from BHK-21 cell culture fluid concentrates or mouse serum. Infective virions prepared from mouse brain or liver banded at a buoyant density of 1.17 to 1.18 g/ml. These density differences, along with observed differences in reactivity with protamine and in rate of neutralization, are consistent with the interpretation that these are related to the problem of whether the source preparations of Oriboca represented primarily intracellular or extracellular particles.